EFFECT OF CD ACCUMULATION ON GROWTH AND BIOLOGICAL ACTIVITY OF MERWILLA PLUMBEA (HYACINTHACEAE) Â€“ A WIDELY USED MEDICINAL PLANT - Street, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Merwilla plumbea (Lindl.) Speta is one of the most popular plant species sold at medicinal markets in South Africa. Due to its high demand, M. plumbea is highly recommended for cultivation. Cadmium (Cd) content in the soil has drastically increased due to pollution and is an important metal to consider in terms of food-chain contamination. The aim of this study was to determine Cd uptake and accumulation and its effect on growth and antibacterial activity in M. plumbea. Cadmium (2, 5 or 10 mg l-1) was supplied to the growth media of potted M. plumbea plants for 6 weeks after which various growth parameters were recorded. Elemental concentration (mg kg-1) was determined using inductively coupled plasma-optical emission spectrometry (ICP-OES). Plant extracts were bioassayed against two Gram-positive and two Gram-negative bacteria using the microdilution method for minimum inhibitory concentration (MIC) determination. Compared with control, Cd had a negative effect on the growth parameters of M. plumbea. The medicinally used bulbs accumulated Cd 7.1, 5.9 and 11.6 mg kg-1 when supplied with Cd at 2, 5 and 10 mg l-1 respectively. When supplied with Cd at 10 mg l-1, M. plumbea bulbs showed higher antibacterial activity against three bacterial species. However, compared to control, no change in activity was seen against E. coli. Due to Cd accumulation in M. plumbea, consumer safety may be compromised. In addition, both horticultural yield and phytochemical composition may be negatively affected when grown in Cd-contaminated soils.